Cervical lymphocele: A rare complication following salvage surgery for ocular adnexal apocrine adenocarcinoma. A case report and review of the literature - Hauer, Lukas; Gencur, Jiri; Posta, Petr; Kasl, Zdenek; Rusnak, Stepan; Skalova, Alena; Chalupova, Miroslava; Liska, Jan; Merglova, Vlasta (Biomedical papers, 2022)
Background. An ocular adnexal apocrine adenocarcinoma (OAAA) is an extremely rare, but potentially aggressive and life-threatening tumor with ill-defined management based only on recommendations from a limited number of reported cases. The development of cervical lymphocele following neck dissection is a very rare complication, but one with well established methods for prevention and treatment. Here we describe a previously unreported case of salvage surgery including neck dissection for OAAA in addition to an emergence of cervical lymphocele. A literature review of current knowledge on both pathological conditions is included. Methods and Results. A 58-year-old man suffering from OAAA, previously treated with multiple eye-sparing excisions and adjuvant proton therapy, underwent salvage surgery for locoregional recurrence of the tumor. A partial orbitectomy with orbital exenteration, primary reconstruction and left-sided neck dissection was performed. The procedure was complicated by a cervical lymphocele resolved after the surgical therapy. The patient remained disease-free during the one-year follow-up. Conclusion. OAAA is a locally aggressive tumor with potential to local or distant metastatic spread. Whole-body staging, regular clinico-radiological follow-up and stage-dependent therapy with surgery as the first-choice treatment is required. A cervical lymphocele as a complication of especially left-sided neck dissection is managed with a conservative or surgical therapy according to the level of lymph leakage, extent and localization of lesions, presence of local or systemic disorders and the period from primary surgery.
Keywords: cervical lymphocele; thoracic duct injury; neck dissection; adnexal tumor; apocrine adenocarcinoma; orbit; salvage surgery